Effect of Al3+ on the photoluminescence and radioluminescence properties of Mn2+-Doped high silica glass. Issue 14 (15th July 2022) - Tao, Yiting; Ma, Xiben; Wang, Jingang; Du, Ying; Wang, Panting; Chen, Danping
Abstract: Mn 2+ /Al 3+ -, Eu 2+ /Mn 2+ -, and Eu 2+ /Mn 2+ /Al 3+ -doped high silica glasses were prepared to investigate their photoluminescence and radioluminescence properties. Particularly, the effect of Al 3+ on the energy transfer from Eu 2+ to Mn 2+ and the regulation law of Mn 2+ luminescence properties in Mn 2+ /Al 3+ - and Eu 2+ /Mn 2+ /Al 3+ -doped glasses were investigated. A strategy to improve the radioluminescence intensity of glasses was developed, and the radioluminescence intensity formula was improved. The dispersion caused by Al 3+ improves the luminous intensity of Mn 2+ and lowers the efficiency of the Eu 2+ →Mn 2+ energy transfer in high silica glass. Al 3+ can significantly broaden the excitation spectrum of Mn 2+ by affecting the coordination number of Mn 2+ and changing the field intensity around Mn 2+ ions. Notably, the developed glass can potentially be applied in laser and LED lights. In addition, nonbridging oxygens (NBOs) are considered to be the main factor leading to the low efficiency of glass radioluminescence. Al 3+ is able to reduce the relative amount of NBOs by forming [AlO4/2 ] −1 tetrahedra, thereby improving the radioluminescence intensity effectively.